Old Mice Accumulate Activated Effector CD4 T Cells Refractory to Regulatory T Cell-Induced Immunosuppression - Harpaz, Idan; Bhattacharya, Udayan; Elyahu, Yehezqel; Strominger, Itai; Monsonego, Alon (Frontiers in Immunology, 2017)
Chronic low-grade inflammation and reduced lymphocyte potency are implicated in the pathogenesis of major illnesses associated with aging. Whether this immune phenotype results from a loss of cell-mediated regulation or intrinsic dysregulated function of effector T cells requires further research. Here we report that, as compared with young C57BL6 mice, old mice show an increased frequency of CD4+CD62L– effector T cells with a dysregulated activated phenotype and markedly increased effector functions. Analysis of the frequency and suppressive function of CD4+FoxP3+ regulatory T cells (Tregs) indicates an increase in the frequency of FoxP3+ T cells with aging which, however, occurs within the CD4+CD25– T cells. Furthermore, whereas Tregs from young and old mice similarly suppress effector T cells from young mice, both have a compromised suppressive capacity of effector T cells from old mice, a phenomenon which is partially recovered in the presence of IL-2-producing CD4+CD62L+ non-effector T cells. Finally, we observed that effector T-cell subsets from old mice are enriched with IL-17A-producing T cells and exhibit intrinsically dysregulated expression of genes encoding cell-surface molecules and transcription factors which play a key role in T-cell activation and regulation. We thus demonstrate an age-related impairment in the regulation of effector CD4 T cells, which may underlie the higher risk for destructive inflammation associated with aging.